Employability and Higher Education: A Category for the Future. Issue 163 (3rd September 2019) - Boffo, Vanna
Abstract: This chapter sets out to introduce some theoretical reflections on the employability construct in adult and higher education. At the same time, it illustrates some perspectives for educational action through the presentation of career service activities aimed at the development of transversal skills.